Philippines Quarterly Update, September 2010 : Stepping Up Reforms to Sustain Growth - World Bank (Washington, DC, 2017)
The Philippine economy recovered strongly from the global recession owing to a combination of transitory and permanent, as well as global and idiosyncratic factors. Similar to its regional peers, the recovery was partly driven by the rebound in global trade and domestic consumption linked to sharp increases in consumer confidence. In the Philippines, growth was also spurred by two domestic and temporary factors-continued fiscal policy easing and election-related spending-and a structural one, namely the acceleration in global outsourcing which benefited the country's business process outsourcing sector and associated sectors such as construction. The economy is projected to grow by 6.2 percent in 2010 and by 5 percent in 2011, with large but broadly balanced risks. While inflation expectations are under control, the prospects of large short-term capital inflows partly linked to renewed quantitative easing by key G7 central banks are complicating monetary policy at a time when the economy no longer needs accommodative monetary policy. The first budget of the Aquino government could be a turning point for the Philippines in the public finance area. The 2011 budget changes current dynamics in two critical areas: the (structural and cyclical) fiscal policy stance and the quality of public finances. This "reform budget" renews the fiscal consolidation effort-albeit modestly and contains significant reform measures aimed at improving spending efficiency, transparency and accountability of the budget. For the 2011 budget to indeed turn the country away from a weak fiscal position, inconsistent spending efficiency, and significant gaps in public expenditure and financial accountability, efforts initiated in this budget will have to both be sustained over time and expanded. Strengthening revenue mobilization-through a modern tax system with efficiency and equity at its core-would enable future budgets to scale up spending needed to generate inclusive growth.